2001
DOI: 10.1136/vr.148.9.273
|View full text |Cite
|
Sign up to set email alerts
|

Clinical recognition and treatment of bovine cutaneous actinobacillosis

Abstract: Hypomagnesaemic tetany and composition ofbody fluids. Use of vitreous for the postmortem diagnosis of hypomagnesaemia. Annales Universitatis Mariae Curie Sklodowska. Sectio DD, Medicina Veterinaria 51, 179-198 TODD, J. R. (1965) The influences of soil type on the effectiveness of single dressings of magnesia in raising pasture magnesium content and in controlling hypomagnesaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 4 publications
1
15
0
1
Order By: Relevance
“…Due to the difficulties in the bacteriological diagnosis, histopathological examination of biopsies is usually helpful for the diagnosis of actinobacillosis (Milne et al 2001). The histopathological changes observed in the skin biopsy from the affected bull, were similar to the described in previous reports.…”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…Due to the difficulties in the bacteriological diagnosis, histopathological examination of biopsies is usually helpful for the diagnosis of actinobacillosis (Milne et al 2001). The histopathological changes observed in the skin biopsy from the affected bull, were similar to the described in previous reports.…”
Section: Resultssupporting
confidence: 62%
“…Sensitivity test confirmed that the A. lignieresii isolated from animal B was streptomycin and sulfonamide-sensitive, antibiotics usually used to treat these cases (Campbell et al 1975, Radostits et al 2007). Penicillin is also indicated for the treatment for actinobacillosis (Radostits et al 2007); however the isolate in this outbreak resulted penicillin-resistant, which has been reported before (Milne et al 2001). Other antibiotics identified as effective in controlling the growth of this particulate isolate could contribute with useful information about Actinobacillus treatment in other cases in different species.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations